2004
DOI: 10.4049/jimmunol.173.1.402
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of H-2Kb and Kbm8 Complexed to a Herpes Simplex Virus Determinant: Evidence for a Conformational Switch That Governs T Cell Repertoire Selection and Viral Resistance

Abstract: Polymorphism within the MHC not only affects peptide specificity but also has a critical influence on the T cell repertoire; for example, the CD8 T cell response toward an immunodominant HSV glycoprotein B peptide is more diverse and of higher avidity in H-2bm8 compared with H-2b mice. We have examined the basis for the selection of these distinct antiviral T cell repertoires by comparing the high-resolution structures of Kb and Kbm8, in complex with cognate peptide Ag. Although Kb and Kbm8 differ by four resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 40 publications
3
18
0
Order By: Relevance
“…This conformational alteration of Arg 62 also has been observed by others in two HLA-B8 structures (Fig. 5B) (37), one of which bound to a peptide with P1-Gly and its Arg 62 is at position 1, whereas in the other, the P1-Phe sterically forces the Arg 62 away to position 2 where it can engage and trigger various TCRs (38). Taking these previous findings into consideration, we hypothesized that in our structure, the acetyl moiety would provide a similar stereochemical effect as the phenyl group of Phe and that the Arg 62 at position 2 might contact with an incoming TCR.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…This conformational alteration of Arg 62 also has been observed by others in two HLA-B8 structures (Fig. 5B) (37), one of which bound to a peptide with P1-Gly and its Arg 62 is at position 1, whereas in the other, the P1-Phe sterically forces the Arg 62 away to position 2 where it can engage and trigger various TCRs (38). Taking these previous findings into consideration, we hypothesized that in our structure, the acetyl moiety would provide a similar stereochemical effect as the phenyl group of Phe and that the Arg 62 at position 2 might contact with an incoming TCR.…”
supporting
confidence: 87%
“…7C, 7D). HLA consensus Glu 58 is retained in most TCR engagement (42), Arg 62 and Gln 65 invariably interacts with the TCR CDR1a or CDR3a loops whenever present on the MHC (37,42). These analyses indicated that not only the acetyl moiety but also the altered residues of MHC class I are highly accessible for interaction with CDR loops of an incoming TCR.…”
Section: Potential Influence Of N-acetylation On T Cell Engagementmentioning
confidence: 92%
“…Substitution of P1-Glu with Asp was tolerated by TRBV10-3 and TRBV28, whereas other substitutions at P1 led to a significant reduction in binding. This effect is possibly attributable to the impact the substitutions have on the conformation of the polymorphic Arg 62 , which has been shown to be sensitive to the residues within the P1 pocket (39). Substitution of the solvent-exposed residues in the bulge of the peptide (P5, P6, and P7) was critical to the specificity of TRBV10-3, whereas TRBV28 was more affected by substitutions at P4 -P6.…”
Section: Discussionmentioning
confidence: 99%
“…1a), it was critical for recognition by this TCR (Fig. 3, a-e), and only an aspartic acid residue was tolerated as , a residue known to be important in TCR ligation (39). The highly prominent central P5-Gln-P6-Gly-P7-Gln residues are possible contact sites for these immunodominant TCRs since the majority of amino acid replacements led to greatly reduced CTL lysis.…”
Section: Fine Specificity Of Tcr Interaction: Accommodation Of the 11mentioning
confidence: 97%
“…The SL8 peptide of HSV is presented equally well by both the wt H2K b and the mutant H2-K bm8 MHC class I glycoproteins, which differ by four aa in the peptide-binding groove (Webb et al, 2004). Comparison of the wt B6 and congenic H2-K bm8 mutant strains showed that the wt mice were much more susceptible to HSV infection.…”
Section: Consequences Of Tcr Diversitymentioning
confidence: 99%